Development and Validation of a Reversed-Phase Liquid Chromatographic Method for Analysis of Rofecoxib in Human Plasma - Krishnaiah, Y.S.R.; Srinivasa Rao, G.; Bhaskar, P.; Shyale, S.S. (Asian Journal of Chemistry, 2010)
High performance liquid chromatographic method was developed for the estimation of rofecoxib in human plasma. Varying amounts of rofecoxib (5 to 400 ng) and fixed quantity of nimesulide (500 ng) were added to blank plasma (0.5 mL) and extracted with dichloromethane. The mixture was centrifuged, organic layer was separated, evaporated to dryness under vacuum and reconstituted with 0.1 mL of methanol. Twenty microlitres of this solution was injected into reverse phase C-18 column using a mobile phase consisting of methanol and water (consisting of 0.04% triethylamine and 0.15% glacial acetic acid) in the ratio of 50: 50 v/v and the eluents were monitored at 272 nm. The method was validated for its linearity, precision and accuracy. The calibration curve was linear in the range of 5 to 400 ng/0.5 mL of plasma. The intra- and inter-day variation was found to be less than 2.3% indicating that the method is highly precise. The mean recovery of rofecoxib from plasma samples containing 50 or 100 ng/mL of the drug was 95.66%. There was no interference of either the drug metabolites or plasma constituents with the proposed HPLC method for the estimation of rofecoxib in human plasma. Due to its simplicity, sensitivity, high precision and accuracy, the proposed HPLC method may be used for biopharmaceutical and pharmacokinetic evaluation of rofecoxib formulations.